Long-Term Outcomes of Allogeneic Stem Cell Transplantation for Relapsed/Refractory Hodgkin and Non-Hodgkin Lymphoma: Multi-center Experience from Turkey - Uysal, Ayse; Soyer, Nur Akad; Ozdogu, Hakan; Goker, Hakan; Cinar, Olgu Erkin; Deveci, Burak; Vural, Filiz (Springer India, 2025)
This multicenter retrospective study evaluated the efficacy of allogeneic hematopoietic stem cell transplantation (allo-HSCT) on survival and safety in patients with relapsed/refractory (R/R) Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL). A total of 110 patients with R/R HL or NHL who underwent allo-HSCT between July 2007 and October 2022 at 7 adult stem cell transplant centers were evaluated. Progression-free survival (PFS), graft versus host disease-free survival (GRFS), and overall survival (OS) were the primary endpoints, and NRM was the secondary endpoint. Forty-one (37.3%) of the total patients were diagnosed with HL, 69 (62.7%) with NHL. The median age at the time of allo-HCT was 39.5 years (16-67), of which 66 (60%) were male. The median follow-up was 67.5 +/- 8.1 months, and the rates of 5-year OS, PFS, and GRFS were 38.4%, 37%, and 34.8%, respectively. On multivariate analysis, CR/PR disease status after allo-HCT was significantly associated with longer PFS (HR: 13.47, 95% CI: 5.80-31.26, p = 0.000) and OS (HR: 5.23, 95% CI: 2.93-9.34, p = 0.000). CR/PR disease status after allo-HCT (HR: 5.79, 95% CI: 3.22-10.40, p = 0.000) and grade 1-2 acute GvHD (HR: 2.33, 95% CI: 1.25-4.35, p = 0.008) were significantly associated with longer GRFS. The 5-year cumulative incidence of NRM was 24.8% (95% CI, 12.5-36.7). The most common conditioning regimen was reduced intensity. Transplant outcomes are not influenced by disease subtype. However, the achievement of a CR/PR response after allo-HCT significantly prolongs OS, PFS and GRFS. In addition, the presence of acute grade 1-2 GvHD was found to be another factor prolonging GRFS. These results support the feasibility of allo-HCT, especially in heavily treated patients.
Keywords: Allogeneic hematopoietic stem cell transplantation; Graft versus host disease-free relapse-free survival; Lymphoma; Progression-free survival; Overall survival